Cemented tungsten carbides production, properties, and testing - Upadhyaya, G. S. (Noyes Publications, 1998)
Written by an international expert, this book covers the processing, microstructure, and properties of cemented tungsten carbides. It is divided into 18 chapters covering wide areas from crystal structure to phase equilibria, production of metal and carbide powders, and much more. This book is ideal for researchers, plant engineers, and senior level students in metallurgical/mechanical/materials engineering who are interested in cemented carbides. There is no parallel book in print.
Keywords: Metal-cutting tools.; Tungsten carbide.; Titanium carbide.; elektronické knihy; electronic books